Galileo - Cavani, Liliana; Onofri, Fabrizio; Contini, Alfio; Beltschew, Iwan; Cusack, Cyril; Kalojantschew, Georgi; Ballista, Gigi (CG Home Video, 2013)
Cavani's second feature, a film that makes an impassioned plea for the primacy of the evidence of the senses as against a seemingly undentable wall of dogma and passively accepted consensus opinion. And the plea is articulated in the early part of the film with real urgency, fervour and individuality. The impenetrable, monolithic quality of state-authenticated truth is wittily rendered in the rigid curlicues and ostentatious grandeur of Papal architecture, and the argument is convincingly developed around the person of Giordano Bruno (Kolaiancev), Galileo's fellow scientist and martyr. The film, however, becomes a lot more conventional and less passionate on Bruno's death, and Cavani is unable to solve the perennial Galileo problem: he (played here by Cusack) turns by degrees into an unastonishing symbol. [www.timeout.com]